2021
DOI: 10.1111/jppi.12384
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare of Persons With Complex Developmental Disabilities From Three European Experiences: France, Italy, and Norway

Abstract: Background: The healthcare pathway of persons with complex developmental disabilities differs by country, depending both on the specificities of the associated healthcare system and the related societal views. In 2017, the French National Organization of Solidarity for Autonomy entrusted to a group of French experts with a specific mission to analyze three European experiences. Specific Aim: The aim of this article is to report the similarities and differences in the healthcare pathways of persons with complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…While there is a strong expectation from families for access to more flexible, evolutive and diversified care modalities (e.g., day or temporary respite care), the current levels of human, financial and technical support are insufficient. 12 The results of theme 5 showed that although parents embraced the view of disability as a medical issue by seeking medical recognition and various forms of therapies, their unmet needs due to confrontation with relational and sociostructural barriers led them to develop resistance to social and societal oppression of their child and people with disabilities. 17,45 Parents discussed sociostructural barriers and challenged the limits placed on their children by emphasizing the importance of focusing on the children's potential and abilities rather than their limitations, providing them with opportunities, and advocating for their social and societal inclusion.…”
Section: Themes Identifiedmentioning
confidence: 99%
See 2 more Smart Citations
“…While there is a strong expectation from families for access to more flexible, evolutive and diversified care modalities (e.g., day or temporary respite care), the current levels of human, financial and technical support are insufficient. 12 The results of theme 5 showed that although parents embraced the view of disability as a medical issue by seeking medical recognition and various forms of therapies, their unmet needs due to confrontation with relational and sociostructural barriers led them to develop resistance to social and societal oppression of their child and people with disabilities. 17,45 Parents discussed sociostructural barriers and challenged the limits placed on their children by emphasizing the importance of focusing on the children's potential and abilities rather than their limitations, providing them with opportunities, and advocating for their social and societal inclusion.…”
Section: Themes Identifiedmentioning
confidence: 99%
“…In contrast to the extensive deinstitutionalization processes of other European countries, the French system relies on institutional settings that aim to offer graduated responses adapted to the severity of the person's health condition (rehabilitation centres, residential facilities [RFs], home care). 12 However, these options are not necessarily adequate and may lack fluidity (e.g., lack of proper general care coordination, imperfect geographic coverage, lack of space in adult care facilities). [12][13][14] A better understanding of parents' experiences of parenting their child with PIMD in this context is necessary to support them more effectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with this multiple-case study we believe that we have a represented the heterogeneity of HISs used: ECD vs EPD, scale, profession, and time of introduction. This study was limited to Dutch HISs, as the organization of care for people with ID differs largely between countries [63,204,205]. HISs suitable for care for people with ID might also be useful for other populations in long term care, such as the elderly, and people who require a long term stay in psychiatric institutions.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…The results may also be transferred to other forms of long-term care, where data registration is similar. Although the organization of care is different between countries [63,204,205], the generic ideas about merging data from different HISs can also be applied there. From the beginning of this thesis, the complete care landscape of Dutch ID care was included to incorporate the wide variety of caregivers involved, and HISs used.…”
Section: Reflection On This Thesismentioning
confidence: 99%